The Influence of Social Media Marketing on Brand Loyalty through Customer Engagement as a Mediating Factor - Sheren Pramana; Ching-Tsung Jen (Penerbit Jurnal Indonesia, 2024)
This study explores how social media marketing affects brand loyalty through customer engagement as a mediating factor in media/news company. This study focuses on Nihao Indonesia, a media platform that provides Indonesian news and content in Taiwan. The research objective is analyzing how social media marketing affects consumer interaction on Nihao Indonesia's Instagram account in order to enhance brand loyalty. A survey was conducted through Google Forms utilizing purposive sampling, distributed to 115 respondents. Structural equation modeling (SEM) was employed to examine the data. The research outcomes demonstrate a significant, positive correlation among the three variables. The findings are expected to offer hands-on knowledge for media companies on optimizing marketing endeavors on social media to make customers more engaged and loyal to a brand.